2018
DOI: 10.1186/s13018-018-0893-z
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis between Orthofix® external fixator and different K-wire configurations for pediatric supracondylar humerus fractures

Abstract: BackgroundClosed reduction and percutaneous fixation are considered as the optional treatments for displaced supracondylar humerus fractures. However, there was no published report about the biomechanical analysis in Orthofix® external fixator. In this study, we developed a model of supracondylar humerus fractures and compared the biomechanical analysis of external fixator and different K-wires configurations in order to evaluate the stability of external fixator in supracondylar humerus fractures.MethodsWe de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
(25 reference statements)
0
6
0
1
Order By: Relevance
“…[33] In biomechanical study of external fixator, Huang [31] found that the external fixator seemed to be superior to plate fixation in load bearing and resistance to torsional stress, the ultimate bearing capacity and load bearing were higher in the external fixator group (145.16 ± 17.42 N and 140 N, respectively) than plate group (120.21 ± 13.15 N and 69.63 ± 25.16-90.78 ± 17.18 N, respectively), and in the resistance to torsional stress, the external fixator's torque fluctuated (within 1 Nm) more evenly distributed than plate's torque (1-5 Nm), and external fixation provided the better rigidity. Li et al [30] also found that linking together the ends of fixation wires with external fixator could provide enough stability and could enhance the rotational stiffness of the construct. Lollino et al [29] reported that external fixator can achieve a rigid fixation in the treatment of PPHFs.…”
Section: Discussionmentioning
confidence: 99%
“…[33] In biomechanical study of external fixator, Huang [31] found that the external fixator seemed to be superior to plate fixation in load bearing and resistance to torsional stress, the ultimate bearing capacity and load bearing were higher in the external fixator group (145.16 ± 17.42 N and 140 N, respectively) than plate group (120.21 ± 13.15 N and 69.63 ± 25.16-90.78 ± 17.18 N, respectively), and in the resistance to torsional stress, the external fixator's torque fluctuated (within 1 Nm) more evenly distributed than plate's torque (1-5 Nm), and external fixation provided the better rigidity. Li et al [30] also found that linking together the ends of fixation wires with external fixator could provide enough stability and could enhance the rotational stiffness of the construct. Lollino et al [29] reported that external fixator can achieve a rigid fixation in the treatment of PPHFs.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding biomechanical stability of different pin configurations, multiple literatures had reported that three crossed pins have the optimal stiffness against all directional forces, followed by two crossed pins and two lateral divergent pins, lastly parallel and convergent pins, respectively (9)(10)(11)(12)30). Zionts et al demonstrated that crossed pin configuration provides the most resistant torsional force (10).…”
Section: Discussionmentioning
confidence: 99%
“…Zionts et al demonstrated that crossed pin configuration provides the most resistant torsional force (10). Liu et al and Li et al also reported that three crossed pins technique provided the most optimal stiffness combination against translational and torsional forces regardless of fracture characteristics (9,30). In our cohort, 5% of lateral-entry only technique (1 of 20) subjected to re-displacement at follow-up, while only 1% of crossed pin technique (1 of 71) loss reduction.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, EF has been the subject of biomechanical stability testing. In this regard, Li et al published an analysis comparing different k-wire configurations and external fixation in your Journal in 2018 [ 2 ]. They concluded: “External fixator could provide enough stability for pediatric supracondylar humerus fractures without the injury of the ulnar nerve.…”
mentioning
confidence: 99%
“…They concluded: “External fixator could provide enough stability for pediatric supracondylar humerus fractures without the injury of the ulnar nerve. Besides, it could enhance the rotational stiffness of the construct in rotation loading to avoid the complication of cubitus varus” [ 2 ]. In the discussion section, they state that “there have been no published reports of biomechanical analysis in the external fixator in supracondylar humerus fractures” [ 2 ].…”
mentioning
confidence: 99%